Survey on Blockchain-Based IoT Payment and Marketplaces - Amila Saputhanthri; Chamitha De Alwis; Madhusanka Liyanage (IEEE Access, 2022)
The ever-growing smart applications will expand the Internet of Things (IoT) ecosystem to connect over 75 billion devices by 2025. IoT ecosystems comprise sensors that act as data suppliers and applications where monetary transactions are required to compensate the data producers. This signifies the importance of IoT payments and marketplaces to facilitate micro-transactions of billions of connected devices in the IoT ecosystem, which is heterogeneous, decentralized, and diverse. However, realizing such an ecosystem raises multiple challenges such as overcoming poor inter-operability, resource constraints, and security and privacy vulnerabilities of IoT devices and platforms. Blockchain is a Distributed Ledger Technology (DLT) that can be identified as a potential solution to overcome the challenges in realizing IoT payments and marketplaces. This is due to the characteristics of blockchain such as decentralization, traceability, immutability, and non-repudiation. This paper presents a comprehensive survey on blockchain-based IoT payments and marketplaces. This paper provides a brief introduction to the concepts of IoT payments and IoT marketplaces. Then the technical challenges involved in realizing IoT payment and marketplaces are discussed by highlighting the blockchain-based solutions. Furthermore, blockchain-based smart applications which use IoT marketplace and IoT payment concepts are presented marking the role of blockchain in each of the application. Subsequently, the paper discuss the integration challenges while also highlighting possible solutions. It is envisaged that this paper would shed light on the development of blockchain-based solutions to realize IoT payments and marketplaces.